Pembiayaan Defisit Anggaran Pembangunan dan Stabilitas Efisiensi Pengeluaran Investasi Swasta - Kuncoro, Haryo (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2002)
This research analyzes t he impact of fiscal policy on economic growth in the case of Indonesia. The analysis is based on the relationship between the fiscal policy and the efficiency of private capital-output ratio (ICOR). The estimation result shows that the fiscal-policy has on the change of the ICOR. Consequently, the private investment is more efficient due to the deficit fiscal allocated on the development expenditure. Also ,the influence of the fiscal policy on the efficiency of private investment is stable over time. Those results above indicate that the fiscal policy effectively affects to the economic growth.